PERLINDUNGAN TENAGA KERJA TERHADAP PENGATURAN WAKTU KERJA DI PT. QUALITY SOLUTION - Fani, Said; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Employment protection against working time at PT. Quality Solution needs supervision, this is caused because there are still many entrepreneurs who violate the rules about working time for their workers, the working time arrangements that apply resulted in losses for the workers in due to non-fulfillment of the right workers. Due to the improper application of working time, the Entrepreneur shall be liable for losses suffered by the employee.The issues discussed are Firstly, on how the implementation of labor protection whose working time exceeds working hours is reviewed from Law Number 13 Year 2003 on Labor Affairs, and Secondly how the responsibility of PT. Quality Solution on the rights of workers that are violated in terms of Law Number 13 Year 2003 concerning Employment.The research method used is empirical research, another term used is sociological legal research is also called field research and this research is descriptive. In data collection, the type of data used in this study is primary data and sekuder data, namely directly through respondents (field), Law No. 13 of 2003 on Employment, legal journals and books related to research. This data analysis is done qualitatively and deductively deduced.From the results of research conducted by the author, it was found that the application of such work time for workers already excessive from existing rules, so that it could harm the workers because their rights are not met. So on the basis of this need a very good labor protection and supervision of the implementation of work time by PT. Quality Solution.Keywords: Protection - Labor - Settings - Working Time.